Cryo-EM structure of the diapause chaperone artemin - Parvate, Amar D.; Powell, Samantha M.; Brookreson, Jory T.; Moser, Trevor H.; Novikova, Irina V.; Zhou, Mowei; Evans, James E. (Frontiers in Molecular Biosciences, 2022)
The protein artemin acts as both an RNA and protein chaperone and constitutes over 10% of all protein in Artemia cysts during diapause. However, its mechanistic details remain elusive since no high-resolution structure of artemin exists. Here we report the full-length structure of artemin at 2.04 Å resolution. The cryo-EM map contains density for an intramolecular disulfide bond between Cys22-Cys61 and resolves the entire C-terminus extending into the core of the assembled protein cage but in a different configuration than previously hypothesized with molecular modeling. We also provide data supporting the role of C-terminal helix F towards stabilizing the dimer form that is believed to be important for its chaperoning activity. We were able to destabilize this effect by placing a tag at the C-terminus to fully pack the internal cavity and cause limited steric hindrance.